Tanggung Jawab Negara Terhadap Pelaksanaan Jaminan Kesehatan Dalam Mewujudkan Universal Health Coverage - Mainita Mainita (Fakultas Hukum Universitas Muhammadiyah Aceh, 2018)
Health is a human right that must be protected and considered by the government, because health is also an indicator of community welfare in addition to economic and social. One of the government's efforts to improve public health is to establish hospitals in each region. Health is a human right that must be protected and considered by the government because health is also an indicator of community welfare in addition to economic and social. One of the government's efforts to improve public health is to establish hospitals in each region.